The Palestinian Issue in the Ordinary and extraordinary Summits of the Islamic Conferences 2003-2005 (Journal of the College of Basic Education, 2022)
Palestine is of great importance to the world because of its religious and geographical location; It is a link between the three continents, and is the center of the three religions, Judaism, Christianity and Islam, and this is what made it the focus of the ambitions of the colonial countries that supported the Zionist movement in order to achieve their common goals.The Organization of the Islamic Conference has been linked to the Palestinian cause and the protection of the holy sites, and the most prominent factor in its establishment was the burning of the blessed Al-Aqsa Mosque by the Zionists on August 21, 1969. Especially the Palestinian cause and its developments, as its conferences dealt with the defense of the Palestinian cause and demanded the protection of Islamic sanctities.The study was divided into four axes: the first axis dealt with (the beginnings of the establishment of the Organization of the Islamic Conference), the second axis dealt with (the Organization of the Islamic Conference and the developments of the Palestinian cause), while the third axis dealt with (the Organization of the Islamic Conference and the issue of Jerusalem), As for the fourth axis, it dealt with (support and victory for the Palestinian cause).